Dysbiosis of the Gut Microbiome in Lung Cancer - Zhuang, He; Cheng, Liang; Wang, Yao; Zhang, Yu-Kun; Zhao, Man-Fei; Liang, Gong-Da; Zhang, Meng-Chun; Li, Yong-Guo; Zhao, Jing-Bo; Gao, Yi-Na; Zhou, Yu-Jie; Liu, Shu-Lin (Frontiers in Cellular and Infection Microbiology, 2019)
Dear Editor: We wish to submit a manuscript entitled “Dysbiosis of the gut microbiome in lung cancer ” to Frontiers in Cellular and Infection Microbiology, Microbiome in Health and Disease section, for your consideration to publish as a Research Article. In this study, we examined the gut microbiome between 30 lung cancer patients and 30 healthy controls via next generation sequencing of 16S rDNA to uncover potential biomarkers for early diagnosis and targeted intervention. Previous analyses of the microbe-lung cancer relationship have been focused on lung microbiome. To our knowledge, this is the first study of lung cancer from the perspective of gut microbiome. Our findings support the hypothesis of an lung cancer-specific compositional structure of gut bacterial populations. Our work suggests that the dysbiosis of the gut microbiome in lung cancer as reflected by reduced abundance of Actinobacteria and Bifidobacterium and elevated levels of Enterococcus had facilitated the development of lung cancer and may help develop novel strategies for early prevention and targeted intervention against lung cancer. The authors claim that none of the materials in the paper has been published or is under consideration for publication elsewhere. Thank you very much for your consideration and we look forward to hearing from you soon. Yours Sincerely He Zhuang and Shu-Lin Liu Genomics Research Center Harbin Medical University 157 Baojian Road Harbin, 150081 China